Upaya Meningkatkan Kemampuan Membaca Permulaan melalui Metode Glenn Doman pada Usia 5-6 Tahun - Niyati Niyati; Iys NurHandayani (Lembaga Yasin AlSys, 2026)
Although early reading skills in young children have been widely examined in previous research, studies that specifically investigate the application of the Glenn Doman method as a structured early reading instruction strategy for 5–6-year-old children in early childhood education institutions remain limited. This study aimed to improve the early reading skills of 5–6-year-old children through the implementation of the Glenn Doman method at KB Mamba’ul Ma’arif Belik. A qualitative approach was employed using a Classroom Action Research (PTK) design based on the Kemmis and McTaggart model, conducted over two cycles, with 15 group B children selected through total sampling. Data were collected through structured observation, documentation, and an early reading assessment rubric covering indicators of letter recognition, letter naming, reading syllables, and reading simple words, and were analyzed using qualitative descriptive analysis and percentages. The findings show a significant improvement in children’s early reading skills, as evidenced by an increase in the average score from 1.28 at baseline to 3.55 in the second cycle, as well as a rise in the proportion of children achieving the “Developing as Expected” category from 33.33% to 93.33%. The study concludes that the Glenn Doman method is effective in improving early reading skills in young children and is worthy of recommendation as an engaging early literacy instructional alternative that is well aligned with children’s developmental characteristics in early childhood education institutions.